Development of a high temperature viscometer for semisolid metal processing - Ahmad, Asnul Hadi; Zakri, Ghazali; Romlay, Fadhlur Rahman Mohd; Nik Mohamed, Nik Mohd Zuki; Rashidi, Maarof Mohd; Ishak, M. (2019)
This research presents the works on the development of a high temperature viscometer for semisolid metal processing.The objective of the project are to investigate the effects of pouring temperature and holding time on the formation of globular microstructure and to study the rheological behaviour of resulting microstructure by using new developed high temperature viscometer. Direct thermal method was used to produce feedstock billet and simple parallel plate compression viscometry was used to investigate the rheological behaviour of aluminium in term of viscosity. The feedstock billet was prepared by using direct thermal method. There were three different temperatures were used consist of 685 ̊C, 665 ̊C and 645 ̊C while for holding time at 60s 40s and 20s. The rheological experiement were conducted by assuming the semisolid metal feedstock billet bahaving as Newtonian fluid. The different of semi-solid aluminium temperatures were used in this works were at 570 ̊C and 600 ̊C for rheological behaviour studies. The calculated viscosity number presented the capability of the semi solid metal slurry in filling the mould Furthermore, through parallel compression test presented the required force of semi solid metal slurry for deformation. Direct thermal method resulted, pouring the molten at low temperature close to the liquidus point provided an appropriate formation of globular microstructure. Rheological behaviour of material resulted, the magnitude of viscosity and applied force increases when reduction of semi solid temperature material. Lastly, the lower viscosity results in better movement of material with less machine pressure.